Protein homeostasis in aging and cancer - Chen, Xiao-Qiong; Shen, Tao; Fang, Shao-Jun; Sun, Xiao-Min; Li, Guo-Yu; Li, Yun-Feng (Frontiers in Cell and Developmental Biology, 2023)
Aging is a major risk factor for cancer development. As dysfunction in protein homeostasis, or proteostasis, is a universal hallmark of both the aging process and cancer, a comprehensive understanding of the proteostasis system and its roles in aging and cancer will shed new light on how we can improve health and quality of life for older individuals. In this review, we summarize the regulatory mechanisms of proteostasis and discuss the relationship between proteostasis and aging and age-related diseases, including cancer. Furthermore, we highlight the clinical application value of proteostasis maintenance in delaying the aging process and promoting long-term health.